The Association Between Macula and ONH Optical Coherence Tomography Angiography (OCT-A) Vessel Densities in Glaucoma, Glaucoma Suspect, and Healthy Eyes. Issue 3 (March 2018) - Manalastas, Patricia I. C.; Zangwill, Linda M.; Daga, Fabio B.; Christopher, Mark A.; Saunders, Luke J.; Shoji, Takuhei; Akagi, Tadamichi; Penteado, Rafaella C.; Yarmohammadi, Adeleh; Suh, Min H.; Medeiros, Felipe A.; Weinreb, Robert N.
Abstract : Purpose: To evaluate strength of associations between optical coherence tomography (OCT)-angiography vessel density (VD) measurements in the macula and peripapillary region of the optic nerve head (ONH) with standard structural OCT thickness measures. Materials and Methods: This cross-sectional study included 333 eyes of 219 primary open-angle glaucoma patients, 41 glaucoma suspects, and 73 healthy participants from the Diagnostic Innovations in Glaucoma Study (DIGS) with good quality OCT angiography images. The strength of associations between microvasculature measures in the ONH retinal nerve fiber layer (RNFL) and superficial macula layer was assessed using linear regression models. Associations between ONH and macula VD, and circumpapillary (cp) RNFL thickness and macular ganglion cell complex (mGCC) measures were also evaluated. Results: The strength ( r 2 ) of associations among VD and thickness measures of ONH and macula ranged from 14.1% to 69.4%; all were statistically significant ( P <0.001). The association between ONH and macula whole-image VD ( r 2 =41.0%) was significantly weaker than the relationship between mGCC and cpRNFL thickness ( r 2 =69.4%, P <0.001). Although both cpRNFL and mGCC thicknesses tended to be more strongly associated with ONH VD ( r 2 =39.2% and 26.7%, respectively) than macula VD ( r 2 =27.5% and 17.7%, respectively), differences did not reach statistical significance ( P =0.050 and P =0.113, respectively). Conclusions: The strength of the association of VD with cpRNFL and mGCC thicknesses varies by retinal layer. The weaker association of macula VD compared with ONH VD with tissue thickness may be due to differences in micorovasculature between the macula and ONH.